Asymptomatic Infant With Atypical SCID and Novel Hypomorphic RAG Variant Identified by Newborn Screening: A Diagnostic and Treatment Dilemma - Chitty-Lopez, Maria; Westermann-Clark, Emma; Dawson, Irina; Ujhazi, Boglarka; Csomos, Krisztian; Dobbs, Kerry; Le, Khuong; Yamazaki, Yasuhiro; Sadighi Akha, Amir A.; Chellapandian, Deepak; Oshrine, Ben; Notarangelo, Luigi D.; et al. (Frontiers in Immunology, 2020)
The T-cell receptor excision circle (TREC) assay was designed to detect T-cell lymphopenia (TCL) in newborns, especially to identify severe combined immunodeficiency (SCID). A spectrum of SCID variants and non-SCID conditions that present with TCL are being discovered by SCID newborn screening (NBS) with increasing frequency. Decisions for treatment are influenced by underlying genetic abnormalities. Recombination-activating gene (RAG) deficiency is one the most common causes of classical and atypical SCID and other conditions with immune dysregulation. This case report aims to highlight how NBS can expedite identification of an asymptomatic newborn with a novel hypomorphic RAG variant and a controversial immune phenotype that required in depth immune evaluation to confirm that the abnormal RAG genotype is linked to the disease and justify definitive therapy with hematopoietic stem cell transplantation (HSCT). Following identification of newborns with out of range TREC levels, the diagnostic approach followed at our center includes lymphocyte subset enumeration by flow-cytometry, quantitative serum immunoglobulin levels, lymphocyte proliferation upon mitogen stimulation and next generation DNA sequencing to search for genetic variants associated with SCID. For babies in whom novel RAG gene variants are detected, we also test for immune biomarkers, and if feasible, analyze the recombinase activity of the novel RAG variants by functional assays and T and B-cell receptor repertoire. We identified and validated pathogenicity for compound heterozygous hypomorphic RAG1 variants in an asymptomatic newborn with undetectable TRECs and controversial immunological phenotype with severe TCL, but normal B cell count and lymphocyte proliferation upon mitogen stimulation. Due to the potential for severe complications with infection and immune dysregulation, the patient underwent a matched unrelated HSCT and is doing well 15 months post-HSCT. In conclusion, partial RAG deficiency can be detected by NBS in some cases such as ours. In case of an atypical immune phenotype and novel RAG gene variants, in vivo and in vitro studies are needed to confirm causative association and expedite treatment with HSCT due to risk of serious infection and non-infectious complications.